2008
DOI: 10.1103/physrevb.77.115112
|View full text |Cite
|
Sign up to set email alerts
|

Pfaffian pairing and backflow wavefunctions for electronic structure quantum Monte Carlo methods

Abstract: We investigate pfaffian trial wave functions with singlet and triplet pair orbitals by quantum Monte Carlo methods. We present mathematical identities and the key algebraic properties necessary for efficient evaluation of pfaffians. Following upon our previous study, 1 we explore the possibilities of expanding the wave function in linear combinations of pfaffians. We observe that molecular systems require much larger expansions than atomic systems and linear combinations of a few pfaffians lead to rather small… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 56 publications
1
116
0
Order By: Relevance
“…Results for canonical and natural orbitals are given. [72][73][74][75][76][77][78][79]). However, the most popular one is certainly the Jastrow-Slater trial wavefunction expressed as a short expansion over a set of Slater determinants multiplied by a global Jastrow factor describing explicitly the electron-electron and electron-electron-nucleus interactions and, in particular, imposing the electron-electron cusp conditions associated with the zero-interelectronic distance limit of the true wavefunction.…”
Section: B Generalization: the G1 Setmentioning
confidence: 99%
“…Results for canonical and natural orbitals are given. [72][73][74][75][76][77][78][79]). However, the most popular one is certainly the Jastrow-Slater trial wavefunction expressed as a short expansion over a set of Slater determinants multiplied by a global Jastrow factor describing explicitly the electron-electron and electron-electron-nucleus interactions and, in particular, imposing the electron-electron cusp conditions associated with the zero-interelectronic distance limit of the true wavefunction.…”
Section: B Generalization: the G1 Setmentioning
confidence: 99%
“…4 For the QSL states with equal-flavor pairing (fwave, p+ip), the wave function is a product of three Pfaffians, 60,61 …”
Section: Appendix B: Fermionic Wave Functionsmentioning
confidence: 99%
“…59 This allows for efficient evaluation of determinants and Pfaffians with rows and/or columns replaced or removed. 22,61,62 To update the inverse of an anti-symmetric matrix with a row and column replaced, we use the Sherman-Morrison algorithm 63 twice, followed by anti-symmetrization of the matrix. This procedure greatly improves the numerical stability of the update.…”
Section: Appendix B: Fermionic Wave Functionsmentioning
confidence: 99%
“…Introduced fixed-node errors can be reduced by expanding the trial wave function in multi-determinants 12,14 or by using the backflow correlation corrections [52][53][54][55] , or both. Previously, it was found that the QMC calculations for the closed shell jellium spheres 18 did not suffer from large fixed-node errors (by comparing to FN-DMC results with small multi-determinant expansions 17 ).…”
Section: A Tests and Validationsmentioning
confidence: 99%